ACCESSIBILITY OF INTERNATIONAL WEBPAGES:A PRELIMINARY SURVEY - Rout, Nachiketa; Amarnath, Reegan; Chandramohan, Neeradha (International Journal of Research -GRANTHAALAYAH, 2014)
The paper surveys the extent to which the international webpage’s applied accessibility statements. Methodology includes thirty one international websites have been evaluated for 17 accessibility features prescribed in the accessibility statement by the Directorate of Standardization testing and quality certification (STQC) along with five accessibility features prescribed byWeb content accessibility guidelines (WCAG).The average score obtained was seven. Top scorers were the Ministry of Road and Transport (21), National institute for Empowerment of Person with Multiple Disabilities (16) and Yahoo webpage (12) Bottom scorers were Wikipedia (7), American Speech and Hearing Association (8), Meccawebpage (8) Massachusetts university (6) and International telecommunication union, toolkit for Disables (6).The features which are significantly applied (p<0.05) are Headings, Subheadings, Titles, Tooltip, Connection with social networking and Videos. The feature which were not significantly used by the websites are Skip to main content, icons, Accessibility features, Adjust contrast scheme and Increase text spacing other Twelve features were used in consistently. Hence the accessibility statements which enable merging the digital divide are yet to be appreciated internationally.